Modified PBL Approaches in Nursing English Pedagogy and Their Impacts on Student’s Achievement, Learning Strategies and Motivation - YU, WEI-CHIEH WAYNE; LIN, CHUN-FU Charlie; WANG, JENNY; HO, MEI-HSIN (Advances in Social Sciences Research Journal, 2014)
Successful learning often lies in a defined philosophy of social factors that operate in the framework of individual experience. Constructivism, or constructivist learning has been a philosophical shift in the educational psychology. Problem-based learning (PBL) is a prime example of social constructivism. This quasi-experimental study investigated traditional lecture instruction, PBL, and blended problem-based learning (B-PBL) on students’ academic achievement, motivation orientation, and use of learning strategies. Positive results for the field of education and B-PBL environments have indicated the need for changes in higher education course design. This study also indicates that a combination of factors for instructing course curricula may be extremely beneficial and essential to consider before designing a course. With findings from the study revealing significantly positive results from the B-PBL group over the PBL group and the Traditional group, its impacts on academic achievement and self-regulation should not be overlooked.